RACIAL STUDY OF Macrobrachium macrobrachion (Malacostraca : Palaemonidae) POPULATIONS FROM THREE TROPICAL LAGOONS, SOUTH-WESTERN, NIGERIA - Mosunmola Florence AKINWUNMI; Aderonke Omolara LAWAL-ARE (UNILAG Journal of Medicine, Science and Technology, 2019)
Macrobrachium macrobrachion (Herklots 1851) is one of the largest species of the genus Macrobrachium in Nigerian waters. It is a decapod that has been widely identified in terms of its economic importance and possibility of recruitment into aquaculture. The racial study of brackish water prawn (M. macrobrachion) from Badagry, Lagos and Epe Lagoons was carried out to determine the variation among the populations from the three interconnecting lagoons. Eight morphometric and three meristic characters were studied. The results showed significant differences (P < 0.05) in total length, telson length, carapace length, carapace width, rostrum length, ventral rostrum teeth and the 3rd abdominal somite with no significant differences (P > 0.05) in the egg diameter of the prawns. The variations recorded could be an indication of genetically distinct populations from different water-bodies. It could also be as a result of isolation caused by differences in salinity gradients in the three lagoons.